Effect of Automated Closed-loop ventilation versus convenTional VEntilation on duration and quality of ventilation in critically ill patients (ACTiVE) – study protocol of a randomized clinical trial - Botta, M; Tsonas, AM; Sinnige, JS; De Bie, AJR; Bindels, AJGH; Ball, L; Battaglini, D; Brunetti, I; Buiteman-Kruizinga, LA; van der Heiden, PLJ; de Jonge, E; Mojoli, F; et al. (BioMed Central, 2022)
Background INTELLiVENT–Adaptive Support Ventilation (ASV) is a fully automated closed-loop mode of ventilation for use in critically ill patients. Evidence for benefit of INTELLiVENT–ASV in comparison to ventilation that is not fully automated with regard to duration of ventilation and quality of breathing is largely lacking. We test the hypothesis that INTELLiVENT–ASV shortens time spent on a ventilator and improves the quality of breathing.